EXPERIMENTAL STUDY ON THE PERFORMANCE OF A SPIRAL TYPE HORIZONTAL AXIS WIND TURBINE DUE TO THE EXPANSION OF THE INNER DIAMETER OF THE TURBINE - Wianda, Dhimaz Rifqy; Hamid, Abdul (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2026)
The significant increase in consumption of electricity from fossil fuels encourages the search for renewable energy sources and wind is one of the renewable energy sources which can be utilized using a horizontal axis wind turbine (HAWT). In this case, a drag and lift model with a spiral type was chosen, adjusting to Indonesia's geography with low wind speeds using the wind tunnel testing method. The purpose of this study was to verify the performance of the two nine-blade TASH type spiral models due to the influence of the expansion of the inner diameter of the turbine, namely the normal diameter of 50mm and the expanded diameter of 65mm. The turbine has a rotor length of 120 mm and an outer diameter of 272 mm. Turbine performance is assessed through measured parameters such as actual power value, torque value, rotor speed and power coefficient, torque coefficient, and tip speed ratio (TSR) as non-dimensional parameters. The research was carried out in a series of laboratory tests through a wind tunnel with various wind speeds from 1 m/s to 10 m/s. The test results are then calculated for the Coefficient Power and Coefficient Torque against the Tip Speed Ratio (TSR). From the calculation results produce an effective value with an air gap of 65mm Cp and efficient TSR values at a wind speed of 5 m/s with a rotational speed of 165 rpm with a Ct of 0.31. While the value of Cp and TSR at a wind speed of 5 m/s is 0.072 and 0.23.